All it takes is empathy: how virtual reality perspective-taking influences intergroup attitudes and stereotypes - Chen, Vivian Hsueh Hua; Ibasco, Gabrielle C. (Frontiers in Psychology, 2023)
Research in the past decade has demonstrated the potential of virtual reality perspective-taking (VRPT) to reduce bias against salient outgroups. In the perspective-taking literature, both affective and cognitive mechanisms have been theorized and identified as plausible pathways to prejudice reduction. Few studies have systematically compared affective and cognitive mediators, especially in relation to virtual reality, a medium posited to produce visceral, affective experiences. The present study seeks to extend current research on VRPT’s mechanisms by comparing empathy (affective) and situational attributions (cognitive) as dual mediators influencing intergroup attitudes (affective) and stereotypes (cognitive). In a between-subjects experiment, 84 participants were randomly assigned to embody a VR ingroup or outgroup waiting staff at a local food establishment, interacting with an impolite ingroup customer. Results indicated that participants in the outgroup VRPT condition reported significantly more positive attitudes and stereotypes towards outgroup members than those in the ingroup VRPT condition. For both attitudes and stereotypes, empathy significantly mediated the effect of VRPT, but situational attributions did not. Findings from this research provide support for affect as a key component of virtual experiences and how they shape intergroup perceptions. Implications and directions for further research are discussed.